2021
DOI: 10.1186/s13643-021-01646-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the implementation of mental health recovery into services: a systematic mixed studies review

Abstract: Background Countries around the world have committed in policy to transforming their mental health services towards a recovery orientation. How has mental health recovery been implemented into services for adults, and what factors influence the implementation of recovery-oriented services? Methods This systematic mixed studies review followed a convergent qualitative synthesis design and used the best-fit framework synthesis method. Librarians ran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 146 publications
(316 reference statements)
3
19
0
Order By: Relevance
“…Our research highlights the negative impact that COVID-19, an outer setting factor, had on the implementation of recoveryinnovations into services. Due to most recovery innovations being predicated upon face-to-face interactions and relationship-building [ 71 ], lockdown policies made it impossible to continue implementation as planned. Only one of seven sites was able to continue implementing without interruption by adapting their innovation to a virtual format.…”
Section: Discussionmentioning
confidence: 99%
“…Our research highlights the negative impact that COVID-19, an outer setting factor, had on the implementation of recoveryinnovations into services. Due to most recovery innovations being predicated upon face-to-face interactions and relationship-building [ 71 ], lockdown policies made it impossible to continue implementation as planned. Only one of seven sites was able to continue implementing without interruption by adapting their innovation to a virtual format.…”
Section: Discussionmentioning
confidence: 99%
“…Since the integration and incorporation of the philosophy and tenets of recovery and recovery-oriented practices in MHSA services, the past two decades have seen a huge rise in the number of scholarly and research publications in the field. This has also encouraged the publication of systematic reviews examining the status of the literature in this growing field [ 3 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. This literature suggests that while recovery orientation has become firmly established in the culture of MHSA care and there is a consensus on the critical elements of recovery conceptualizations and the principles of recovery-oriented practice, there are still some controversies regarding three significant issues that have been voiced in the more recent literature [ 36 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some previously identified challenges when implementing recovery-oriented practices include organizational logistics, competing demands and care culture (Cusack et al 2017;Hornik-Lurie et al 2018;Lorien et al 2020;McAllister & McCrae 2017;Waldemar et al 2019). In a recent review, the authors concluded that there were several factors impeding implementation of mental health recovery into services and for transformation to happen there was a need for more general changes across the whole organization (Piat et al 2021).…”
Section: Discussionmentioning
confidence: 99%